Study on molecular mechanism of volatiles variation during Bupleurum scorzonerifolium root development based on metabolome and transcriptome analysis - Yu, Dan; Wang, Wenxue; Huo, Jinhai; Zhuang, Yan; Chen, Yiyang; Du, Xiaowei (Frontiers in Plant Science, 2023)
The root of Bupleurum scorzonerifolium Willd. contains a large amount of volatile oil (BSVO), which shows a variety of biological activities. The yield and quality of volatile oil have been confirmed to depend on plant development. In the present study, B. scorzonerifolium root was collected at germinative, vegetative, florescence, fruiting and defoliating stages, respectively, and BSVO yield, volatile metabolic profile and transcriptome of root collected at the different developmental stages were comprehensively determined and compared. BSVO sustainably accumulated from the germinative to the fruiting stage and slightly decreased from the fruiting to the defoliating stage. A total of 82 volatiles were detected from B. scorzonerifolium root, of which 22 volatiles were identified as differentially accumulated metabolites (DAMs) during the root development. Of these volatiles, fatty acids and their derivatives accounted for the largest proportion. The contents of most major volatiles were highest at the fruiting stage. A large number of differentially expressed genes (DEGs) were detected during B. scorzonerifolium root development, of which 65 DEGs encoded a variety of enzymes and transcription factors regulating the biosynthesis of fatty acids and their derivatives. Further analysis identified 42 DEGs significantly correlated with DAMs, which may be the key genes for the biosynthesis of volatiles. This study is the first to comprehensively report the volatiles variation and its molecular mechanism during B. scorzonerifolium root development, which will provide important cues for future work on determining the harvest time of B. scorzonerifolium root and improving the quality of BSVO.